Improving mathematics teaching and developing teachers through Parallel Lesson Study - Han, Xue (2017)
To understand Chinese students’ high performance on international mathematics assessments, researchers have explored Chinese teachers’ professional development and argued that engaging in school-based teaching research activities, including conducting Chinese lesson study, has played a critical role in improving teaching and learning in mathematics. In recent years an enriched model of Chinese lesson study, parallel lesson study (PLS) has been implemented nationwide to support the reform-oriented curriculum. PLS follows the same cycle of regular lesson study while there are at least two independent lesson study groups (including mathematics specialists and teachers) that develop research lessons of the same mathematics topic simultaneously. This chapter synthesizes the key findings of two research studies on PLS to describe and discuss how PLS contributed to the improvement of teaching that promotes student learning as well as teacher learning. The district PLS addressed developing algebraic reasoning with 7th grade students while the school-based PLS explored learning trajectory-based lessons on division with fractions at 6th grade.